Collaborative acute medical postgraduate–undergraduate simulation: a new multi-modal transition programme for final-year medical students. (2019) - Khawaja, Sanna; Bhalla, Aditya; Patel, Viral; Naleem, Shairana; Suleiman, Abiola; Rangasalen, Nira; Kenny, Anthony
No abstract available